CD63 e CD123 expressão, autoanticorpos IgG e acurácia do teste do soro autólogo em pacientes com urticária crônica - Calamita, Zamir; Antunes, Roseli Nunes da Silveira; Almeida Filho, Odilon Marques de [UNESP]; Baleotti Júnior, Wilson; Calamita, Andrea Bronhara Pelá; Fukasawa, Josianne Thomazini; Cavaretto, Débora de Aguiar (My University, 2012)
Introduction: The autologous serum skin test (ASST) may suggest an autoimmune etiology in chronic urticaria (CU). A new laboratory technique called basophil activation test (BAT) has been currently employed for its diagnosis. Objective: To analyze ASST in relation to BAT as well as to evaluate interleukin 3 (IL3) receptors (CD123) and non-specific immunoglobulin G (IgG) autoantibodies bound to basophils in patients with chronic urticaria. Methods: We studied 33 adults with CU and mean age of 42.5 + 14 years. After stimulation by serum from patients with CU, CD63 expression on basophils from one atopic donor was analyzed by flow cytometry. Furthermore, we investigated CD123 and IgG autoantibody expressions. Results: The odds ratio (OR) between ASST and BAT was 1.00 (95% confidence interval [CI]: 0.22 to 4.5). The ASST for autoimmune CU diagnosis showed an accuracy of 54.5%, sensitivity of 66%, specificity of 33%, positive predictive value of 63%, and negative predictive value of 36%. There was no statistical difference between the studied groups as to mean non-specific IgG and CD123 expressions (for a p < 0.05). Discussion: This study demonstrated that ASST has low accuracy in the diagnosis of autoimmune CU. Concerning other analyzed aspects, there was no statistical difference between positive ASST and negative ASST. Conclusions: Due to insufficient studies in this area and the relevance of this issue, further investigation is required.
CD63 and CD123 expression, IgG autoantibody and accuracy of autologous serum test in patients with chronic urticaria
Keywords: Accuracy; Autologous serum skin test; Basophil activation test; CD123; CD63; Chronic urticaria